Age-Related Modifications in Circulating IL-15 Levels in Humans - Sebastiano Gangemi; Giorgio Basile; Daniela Monti; Rosaria Alba Merendino; Giuseppe Di Pasquale; Ursula Bisignano; Vittorio Nicita-Mauro; Claudio Franceschi (Hindawi Limited, 2005)
Aging is associated to a progressive establishing of a chronic inflammatory state linked to a continuous long exposure to antigens. Since IL-15 stimulates the proliferation of memory T cells and the immunosenescence is characterized by accumulation of memory T cells and exhaustion of naive T cells, we analyzed IL-15 levels in sera from 30 ultralongeval subjects with respect to those from young and old adults. IL-15 levels were assayed by immunoenzymatic methods. Ultralongeval subjects displayed significantly higher IL-15 levels with respect to both young and old controls. No statistical difference was found between old and young controls. These findings may explain, at least in part, the characteristic increase of memory cells in immunosenescence and the capacity of the immune system of centenarians to defend itself from infections through immune-inflammatory responses.